TABA LANGUAGE DIALECT - Afida Wahid,; Ikmal Muhammad,; Andriani, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to study the Taba language dialect and examine internal changes in the Taba language in seven villages in Makyan Dalam sub-district, South Halmahera district.The method in this study uses the diachronic dialectology method and internal reconstruction techniques and bottom-up and top-down approaches based on the theory of diachronic dialectology to explain the variations of the Taba language which are divided into urban dialects and peripheral dialects.The results of the analysis show that the relationship between Taba language dialects shows differences between the WW dialect (Waigitang, Waikyon) which is categorized as a city dialect or Taba cultural center dialect on the one hand, on the other hand the peripheral dialect which reflects the innovation area and the relict area (conservative). The city or cultural center dialect tends to show elements of innovation (renewal), while the peripheral area tends to show relict elements when associated with the reflexes of Taba Prelanguage (PBT) phonemes.